Bright blue electroluminescence of diamond/CeF3 composite films. (November 2016) - Chen, Hai-Jiang; Wang, Xiao-Ping; Wang, Li-Jun; Ke, Xiao-Long; Ning, Ren-Min; Song, Ming-Li; Liu, Ling-Hong
Abstract: Diamond/CeF3 composite film (DCCF) electroluminescence devices was fabricated on highly doping n-type silicon substrates by using plasma chemical vapor deposition techniques and vacuum electron beam evaporation techniques. The films were characterized by field emission scanning electron microscopy (FE-SEM), Energy dispersive spectrum (EDS), X-ray diffraction (XRD) and electroluminescence (EL) spectrum. The EL spectrum of DCCFs shows that a strong broad peaks are located at 440 nm, and its EL brightness of the device can reach 10 cd/m 2 at a forward applied voltage of 120 V. The blue light emitting peak is assigned to the transitions from the excited 5d state to 4f ( 2 F5/2 ) and 4f ( 2 F7/2 ) states of Ce 3+ ions, respectively.